IMPLEMENTASI PENERTIBAN REKLAME DI KOTA DUMAI - Saragih, Loyal Septian Arafat; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Advertisement is media that used to convey a message to another people. Advertisement is used in order to promote a product to consumers. Either delivered orally, visually, or a combination of both. The aim of advertisement is to show the customer what product we want to sold. Advertisement itself has a major contribution to the visual impression of an environment. In addition, it has contributions as Pendapatan Asli Daerah (PAD). Thus, in this time, advertisement aims is more often concerned with retribution than the beauty of city, the security of citizen and safety of the environment.The concept theory that used is the theory of implementation of the policy according to Edward III. The indicators in this study, namely communication, resources, disposition, bureaucratic structure. The informant of this study is the Head of Pamon Praja Unit Dumai, Head of Licensing Agency and the Integrated Services Investment town of Dumai, Dumai Head of the Department of Revenue. The complement informants were staff Administrative Civil Pamong Praja Unit Dumai, Owner of advertisement. This research is a qualitative descriptive study using data collection techniques by observation and interviews were obtained from informants study.Based on the research that has been done and based on the data analysis process has been known, it can be showed that controlling advertisement in Dumai running less good or less than optimal. This condition influenced by many things, whether it is a barrier effect of enforcement rules themselves, from the advertisement owner and the citizen in Dumai. Moreover, it is affected by the communication and coordination is among the official parties themselves.Keywords: Implementation, Control, Advertising